Multiple Sevoflurane Exposures During the Neonatal Period Cause Hearing Impairment and Loss of Hair Cell Ribbon Synapses in Adult Mice - Li, Yufeng; Yu, Huiqian; Zhou, Xuehua; Jin, Lin; Li, Wen; Li, Geng-Lin; Shen, Xia (Frontiers in Neuroscience, 2022)
Abstract Objectives: This study aims to investigate the effects of multiple sevoflurane exposures in neonatal mice on hearing function in the later life and explores the underlying mechanisms and protective strategies. Methods: Neonatal Kunming mice were exposed to sevoflurane for three days. Auditory brainstem response (ABR) and distortion product otoacoustic emission (DPOAE) tests, immunofluorescence, patch-clamp recording, and quantitative real-time PCR were performed to observe hearing function, hair cells, ribbon synapses, nerve fibers, spiral ganglion neurons, and oxidative stress. Results: Compared to control group, multiple sevoflurane exposures during the neonatal time significantly elevated ABR thresholds at 8 kHz (35.42 ± 1.57 vs. 41.76 ± 1.97 dB, P = 0.0256), 16 kHz (23.33 ± 1.28 vs. 33.53 ± 2.523 dB, P = 0.0012), 24 kHz (30.00 ± 2.04 vs. 46.76 ± 3.93 dB, P = 0.0024), and 32 kHz (41.25 ± 2.31 vs. 54.41 ± 2.94 dB, P = 0.0028) on P30, caused ribbon synapse loss on P15 (13.10 ± 0.43 vs. 10.78 ± 0.52, P = 0.0039) and P30 (11.24 ± 0.56 vs. 8.50 ± 0.84, P = 0.0141), and degenerated spiral ganglion neuron (SGN) nerve fibers on P30 (110.40 ± 16.23 vs. 55.04 ± 8.13, P = 0.0073). In addition, the Vhalf of calcium current become more negative (−21.99 ± 0.70 vs. −27.17 ± 0.60 mV, P < 0.0001), exocytosis was reduced (105.40 ± 19.97 vs. 59.79 ± 10.60 fF, P < 0.0001), and Lpo was upregulated (P = 0.0219) in sevoflurane group than those in control group. N-acetylcysteine reversed hearing impairment induced by sevoflurane. Conclusion: The findings suggest that multiple sevoflurane exposures during neonatal time may cause hearing impairment in adult mice. The study also demonstrated that elevated oxidative stress led to ribbon synapses impairment and SGN nerve fibers degeneration, and the interventions of antioxidants alleviated the sevoflurane-induced hearing impairment. Keywords: sevoflurane; hearing impairment; hair cells; ribbon synapse; spiral ganglion neuron nerve fiber; oxidative stress